Optimizing Learning Design for Islamic Religious Education in Islamic Boarding Schools: Efforts to Increase the Intelligence and Academic Quality of Students - Hosaini; Mujamil Qomar; Abad Badruzaman (Institut Attanwir Bojonegoro, 2024)
This research aims to explore the optimization of Islamic Religious Education (PAI) learning designs in Islamic boarding schools in order to improve the intelligence and academic quality of students. The research method used is a literature review system, by examining various relevant literature regarding the application of modern learning methods and technology in the context of Islamic boarding schools. The findings from this research show that the integration of technology-based learning methods, such as Problem-Based Learning and Project-Based Learning, as well as the use of digital media, has succeeded in increasing student engagement and understanding. Islamic boarding schools that adopted this learning design recorded significant improvements in the academic quality and learning motivation of students. The conclusion of this research confirms that optimizing learning design in Islamic boarding schools that combines traditional and modern methods can produce students who are smarter and more knowledgeable. Adequate infrastructure support and teacher training are needed to overcome implementation challenges, so that Islamic boarding schools can continue to produce superior generations who have morals and are ready to face global challenges.